Essay Writing Training For Student Activity Units Research, Devotion, And Language Of Politeknik Negeri Banyuwangi: Pelatihan Menulis Esai Bagi Unit Kegiatan Mahasiswa Riset, Pengabdian, Dan Bahasa Politeknik Negeri Banyuwangi - Moh. Satrio (DPD Jatim Perkumpulan Dosen Indonesia Semesta, 2026)
The low interest in literacy and understanding of essays among students is a sign of a decadence. Students should think critically about literacy to master various information and stay current. Essay writing training aims to raise students' awareness of literacy culture and produce good essays. This two-day activity was conducted in partnership with the research, community service, and language student activity units of the Banyuwangi State Polytechnic. The training included lectures, discussions, and mentoring. The training taught and guided students from an introduction to essays to the proper way to write a good and correct essay. The training resulted in eight essays worthy of publication.